Financial Inclusion, Electronic Payment Methods and Tax Evasion: Economic Analysis and Application in Argentina - Pedroni, Florencia Verónica; Pesce, Gabriela; Briozzo, Anahí (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In contexts of high informality and increasing digitization, businessmen question themselves: is it worth incorporate collections by electronic payment methods to increase sales? How much more would you have to sell to cover transaction costs? How much would the tax costs increase for reporting the additional income generated? In response to such questions, this work aims to describe and compare the payment methods costs and tax costs associated with sales collected through different channels (cash, banking methods and virtual wallets), sensitizing these results in the face of digitization scenarios (increased in revenue by electronic sales) or informality situations (income underreporting). Methodologically, a simulated case study is developed (food microenterprise from Bahía Blanca) in which costs and net results of eleven payment methods are estimated for the two tax regimes in force in Argentina: VAT registered taxpayer and simplified taxpayer. According to the results, in relative terms, the VAT registered taxpayer faces lower transaction costs and higher tax costs, compared to simplified taxpayer. Underreporting of 30% of cash income cuts tax costs by weight of sales in half for both types of taxpayers, although the incentives to evade tax are higher for VAT registered taxpayers and for simplified taxpayers with sales close to the inflection point between the tax regimes. The findings reveal that the main limitation to implement electronic payments in small firms is associated with informality and not with transaction costs, demonstrating that the phenomena of financial inclusion and tax evasion must be addressed jointly.